Pesticide Residues in Animal Products: Problems and its Alternative Prevention - Indraningsih .; Yulvian Sani (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2004)
Pesticides as agrochemicals are used to control plant diseases, however the use of pesticides may cause poisoning for human health and non-target animals, residual formation in animals and crops, and environmental contamination (soils and water). The impacts of pesticide are generally due to excessively or inappropriate use of pesticides. The surveillance on pesticide residues and/or contamination in animal products, crops and environment conducted in West Java and Lampung shows that some pesticide residues were detected in milk from West Java (Bogor and Pangalengan) including lindane, heptachlor, diazinon and endosulfan. In general, the pesticide residues in milk ofBogor were below the maximum residue limits (MRL), but two pesticide residues in milk of Pangalengan: diazinon (239 ppb) and heptachlor (60,3 ppb) appeared to be sufficiently high for human consumption. Some pesticide residues were also detected in meat, liver and fat of cattle in Bogor and Lampung. Both organochlorine and organophosphate residues were detected in samples of Bogor including: lindane (not detected/nd-135,5 ppb) and diazinon (nd-754,4 ppb) in meat; lindane (nd-16,7 ppb), diazinon (nd-969 ppb) and endosulfan (nd-191,8 ppb) in liver; and diazinon (nd-908,1 ppb) in fat. The residue level of diazinon detected in meat, liver and fat appeared to be higher than the MRL level. On the other hand, there was only organochlorine being detected in meat of Lampung. Regarding to pesticide residues being detected in soils, the source of contamination was then suspected from the contaminated soils where fodders being grown (grass, cabbages and corn). By-products of cabbage and corn are commonly used as animal feed for dairy and beef cattle respectively. The organic fanning system can be used as an alternative to minimise agricultural land contamination and pesticide residues in agricultural products. The low pesticide residues in agricultural by-products were able to reduce pesticide residues in animal products (meat and milk). The possibility of pesticide contamination should be taken into account in using agricultural by-products for animal feed to prevent pesticide residual effects in animal products. Key words: Residue, pesticides, minimalization, animal, organic